Glycemic variability is associated with poor outcomes in pediatric hematopoietic stem cell transplant patients. Issue 11 (16th August 2020) - Sopfe, Jenna; Campbell, Kristen; Keating, Amy K.; Pyle, Laura; Liu, Arthur K.; Verneris, Michael R.; Giller, Roger H.; Forlenza, Gregory P.
Abstract: Background: Among pediatric hematopoietic stem cell transplant (HSCT) recipients, abnormal glycemic control is shown to be associated with increased risk of transplant‐related mortality, death from any cause, risk of infection, increased hospitalized, and intensive care days. Independent effects of higher glycemic variability, a component of glycemic control, have not been described. This study aimed to characterize risk factors for, and consequences of, higher glycemic variability in HSCT patients. Procedure: Medical records for a cohort of 344 patients, age 0‐30 years, who underwent first HSCT from 2007 to 2016 at Children's Hospital Colorado were retrospectively reviewed. Glucose coefficients of variation (CV) were analyzed for HSCT days −14 to 0 and 0‐30, and patients were assessed for potential risk factors and outcomes. Results: Roughly one‐third of patients had pre‐HSCT and day 0‐30 glucose CV above the reported healthy adult range. Independent of HSCT type, doubling of pre‐HSCT glucose CV was associated with a 4.91‐fold (95% confidence interval [CI], 1.40‐17.24) increased hazard of infection, as well as increased risk for intensive care hospitalization for allogenic HSCT patients. Multivariable analysis demonstrated that allogeneic HSCT patients had a 1.40‐ and 1.38‐fold (95% CI, 0.98‐1.99 and 1.00‐1.91) increased hazard of death for every doubling of pre‐HSCT and day 0‐30 glucose CV, respectively. Conclusions: Just as with higher mean glucose, higher glycemic variability in the pediatric HSCT population is independently associated with significantly increased morbidity. Additional research is required to evaluate the utility of glucose control to mitigate these relationships and improve HSCT outcomes.